SCTP-aware Link Layer Retransmission Mechanism for Smart-grid Communication Network - Zafar, S.; Ejaz, U. (Engineering, Technology & Applied Science Research, 2016)
The smart grid delivers electricity from suppliers to consumers and uses bidirectional communication to exchange real-time information between supply system and smart meters at the user end. With a combined communication infrastructure, smart grid manages the operation of all associated components to provide reliable and supportable electricity supply. The Neighborhood Area Network (NAN) of smart grid supports bi-directional data transfer between smart meters (installed at customer premises) and control center of the utility company through an aggregator. This communication suffers low throughput and excessive delays due to the Head of Line (HOL) blocking when the Transmission Control Protocol (TCP) is implemented for reliability. In this paper we propose SCTP-aware Link Layer Retransmission mechanism (SCTP-LLR) which augments the Stream Control Transmission Protocol (SCTP) with Link Layer Retransmissions at the aggregator. SCTP-LLR uses the multi-streaming feature offered by SCTP and implements link layer retransmissions at the aggregator to mitigate the effect of HOL blocking. We carried out simulations using Network Simulator and compared the performance of SCTP-LLR against TCP and SCTP. Our results show that SCTP-LLR outperforms both TCP and SCTP in terms of throughput and packet delays and is a promising protocol to be implemented in smart grid NAN for reliable and efficient communication.